Penerapan Pendidikan Multikultural pada Sekolah Dasar - Khaerunnisa, Uun; Darmiyanti, Astuti; Ferianto, Ferianto (Al-Liqo: Jurnal Pendidikan Islam, 2023)
In the midst of the very rapid development of information technology, Indonesia is experiencing a multidimensional crisis including a crisis of morality, ethics and tolerance. We find many cases that occur today such as juvenile delinquency, brawls, bullying etc. One reason is the lack of understanding of the cultural diversity that exists in Indonesia. Cultural diversity should be seen as a gift given by God Almighty as a manifestation of the Sunnatullah which is a force to support each other and build unity, not as an excuse for committing acts of discrimination, suspicion, injustice and human rights violations. Educational institutions have an important role in creating a generation that understands the concept of multiculturalism, where students can be given an understanding and accustomed to thinking and acting in accordance with the concept of multiculturalism. The formulation of the problem in this study is how is the implementation of multicultural education in elementary schools presented in the supporting and inhibiting factors for the implementation of multicultural education and an analysis of the literature on the implementation of multicultural education in elementary schools.